2018
DOI: 10.1016/j.bbmt.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment in Adult T Cell Leukemia/Lymphoma Treated with Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Disease status at allogeneic hematopoietic cell transplantation (HCT) is an important pretransplant prognostic factor of HCT in adult T cell leukemia/lymphoma (ATL); however, other prognostic factors, including comorbidities, were not predictive in small cohort analyses. Several scoring systems (HCT-specific comorbidity index [HCT-CI]/modified European Group for Blood and Marrow Transplantation risk score [mEBMT]) have been adopted to predict HCT outcomes in other hematologic malignancies. We retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Further, we showed that hematopoietic cell transplantation-specific comorbidity index (HCT-CI; Sorror et al, 2005) and EBMT score (Gratwohl et al, 2009) at transplant were reliable prognostic factors in patients with ATL who underwent allo-HCT (Tokunaga et al, 2017). However, the EBMT score was not associated with the risk of non-relapse mortality (NRM) because about 95% of patients with ATL who underwent allo-HCT were over than 40 years of age in the Japanese TRUMP database (Yoshimitsu et al, 2018a). We attempted to develop another new ATL HCT prognostic index (ATL-HCT-PI).…”
Section: Development Of Allo-hct For Atlmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we showed that hematopoietic cell transplantation-specific comorbidity index (HCT-CI; Sorror et al, 2005) and EBMT score (Gratwohl et al, 2009) at transplant were reliable prognostic factors in patients with ATL who underwent allo-HCT (Tokunaga et al, 2017). However, the EBMT score was not associated with the risk of non-relapse mortality (NRM) because about 95% of patients with ATL who underwent allo-HCT were over than 40 years of age in the Japanese TRUMP database (Yoshimitsu et al, 2018a). We attempted to develop another new ATL HCT prognostic index (ATL-HCT-PI).…”
Section: Development Of Allo-hct For Atlmentioning
confidence: 99%
“…We attempted to develop another new ATL HCT prognostic index (ATL-HCT-PI). We determined three independent risk factors, including optimized HCT-CI, donor–recipient sex combination (female donor–male recipient), and older age (≥64 years; Yoshimitsu et al, 2018a). By using these three risk factors, we divided patients into 3 risk groups, namely low, intermediate, and high risk, and then developed a new ATL-HCT-PI, which could be used to stratify NRM and OS rates in patients with ATL according to the three risk groups (2-year NRM of 22.0, 27.7, and 44.4%, and 2-year OS of 47.3, 39.1, and 15.7% for ATL-HCT-PI low-, intermediate-, and high-risk patients, respectively; Yoshimitsu et al, 2018a).…”
Section: Development Of Allo-hct For Atlmentioning
confidence: 99%
“…The cumulative incidences of NRM at 100 days and 1 year after transplantation were 19% (95% CI, 2%‐36%) and 42% (95% CI, 16%‐69%), respectively (Figure A). Recently, Yoshimitsu et al established ATL‐HCT‐PI, a predictive scoring system for NRM in allo‐HCT for ATL patients. ATL‐HCT‐PI consists of three factors: revised HCT‐CI, sex combination (female donor and male recipient), and age 64 years or older.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason for unfavorable OS after allo‐HSCT was higher NRM in our study. Yoshimitsu et al recently reported that three factors, namely, revised HCT‐CI, sex combination (female donor and male recipient), and age 64 years or older, were useful for predicting NRM in ATL patients after allo‐HCT (ATL‐HCT‐PI). In our study, even the low‐risk group defined by ATL‐HCT‐PI had a high NRM of 58%, with the following causes of death: disease relapse/progression (two cases), HHV‐6 encephalopathy, bacterial infection, thrombotic microangiopathy (TMA), and lymphoproliferative disorder (each one case).…”
Section: Discussionmentioning
confidence: 99%
“…Most data favoring alloHSCT over chemotherapy alone originate from retrospective analyses, are limited by selection bias, and show a relatively high transplant-related mortality (TRM) [3,6]. Nevertheless, alloHSCT is the only treatment modality that can achieve long-term remissions or cure, especially for aggressive subtypes, and has demonstrated potential survival advantage [14,15]. Hence, upfront alloHSCT has become the preferred strategy in acute and lymphomatous subtype patients who are transplant-eligible [16,17].…”
Section: Biol Blood Marrow Transplant 25 (2019) E199àe203mentioning
confidence: 99%